"We wish to have good medical care": findings from a qualitative study on reproductive and maternal health of internally displaced women in India. Issue 2 (1st January 2022) - Rajbangshi, Preety R.; Nambiars, Devaki; Srivastava, Aradhana
Abstract: Internally displaced women are underserved by health schemes and policies, even as they may face greater risk of violence and unplanned pregnancies, among other burdens. There are an estimated 450, 000 internally displaced persons in India, but they are not formally recognised as a group. Displacement has been a common feature in India's northeast region. This paper examines reproductive and maternal health (RMH) care-seeking among Bru displaced women in India. The study employed qualitative methodology: four focus group discussions (FGDs) were held with 49 displaced Bru women aged 18–45 between June and July 2018; three follow-up interviews with FGD participants and five in-depth interviews with community health workers (Accredited Social Health Activists – ASHAs) in camps for Bru displaced people in the Indian state of Tripura. All interviewees gave written or verbal informed consent; discussions were conducted in the local dialect, recorded, and transcribed. Data were indexed deductively from a dataset coded using grounded approaches. Most women were unaware of many of the RMH services provided by health facilities; very few accessed such care. ASHAs had helped increase institutional deliveries over the years. Women were aware of temporary contraceptive methods as well as medical abortion, but lacked awareness of the full range of contraceptive options. Challenges in accessing RMH services included distance of facilities from camps, and multiple costs (for transport, medicines, and informal payments to facility staff). The study highlighted a need for comprehensive intervention to improve RMH knowledge, attitudes, and practices among displaced women and to reduce access barriers.